THE SPEAKING ABILITY TAUGHT BY USING BRAINSTORMING - Effendi, Dwi Erlin (PEOPLE: International Journal of Social Sciences, 2015)
Generally, people want to be able to speak their main and express their ideas fluently, but it`s not an easy way to make it comes true. There were many times when they keep silent for knowing nothing what they want to speak. Through this research, the writer attempt to analyze brainstorming effectiveness in speaking to make them speak up. This research is aimed to give us a brief experimental of the speaking ability of the first semester students of Economic and Business Faculty UNISNU Jepara overcome their form and express their ideas in speaking. After the data were analyzed, it can be seen from the result that brain storming is should help the students, overcome their form and express their ideas in speaking that is 85% and average score 80,95 and without using brainstorming is 65% and average score 75,94. However, it`s suggested that it is better for applying brainstorming at the earliest level.